Fatty Amines Embedded Carbon Membranes with Aligned Nanochannels Network: A Device with Extremely High Photothermal Conversion Efficiency toward Solar Energy Harvesting and Storage. Issue 4 (7th January 2022) - Ye, Xingyun; Tian, Zhuoyue; Cao, Xiaoyin; Fan, Yukang; Zhou, Peilei; Wang, Chengjun; Li, Jiyan; Sun, Hanxue; Zhu, Zhaoqi; Liang, Weidong; Li, An
Abstract : The development of phase change materials (PCMs) composites with high light‐to‐thermal energy conversion efficiency is of great importance for solar energy storage. Herein, the preparation of novel PCMs composites by incorporation of fatty amines (FAs) into the carbon membranes (CMs) with aligned nanochannels network is first reported, which is obtained by employing an anodic alumina oxidation membrane as sacrificing template and using polypyrrole and asphalt as carbon precursor via a simple carbonization treatment. The carbonized membranes possess abundant porosity and aligned nanochannels, which is beneficial to harvest solar light combined with their carbon in nature. In addition, organic PCMs, i.e. 1‐Hexadecanamine (HDA, ΔH = 311.1 kJ/kg) and 1‐Aminoheptadecane (AHD, ΔH = 293.0 kJ/kg) can be spontaneously loaded into the nanochannels of CMs by the capillary action and surface tension. The fabricated FAs/CMs composites present an enhanced thermal conductivity ranging from 0.291 to 0.525 W m −1  K −1 . Compared to pure FAs, the thermal conductivities of the PCMs composites are 144.8–357.1% higher than that of the control. Meanwhile, the as‐synthesized FAs/CMs composites also exhibit a remarkable high photothermal energy storage efficiency of up to 93.8%, which is one of the highest values reported to date, making them promising candidates for a broad range of applications in solar energy harvesting, conversion, and storage. Abstract : This article reports the facile fabrication of novel phase change materials composites using carbon membranes as porous supporting materials impregnated with fatty amines for efficient solar energy harvesting and storage. The as‐prepared composites show an extremely high photothermal conversion efficiency of up to 93.8%, making them promising candidates for solar energy harvesting and storage.